Diplogyniidae (Acari: Mesostigmata) associated with Panesthia cockroaches (Blattodea: Blaberidae) - Seeman, Owen D. (Zootaxa, 2012)
Five new Australian species of Paradiplogynium and one new species of Lobogyniella are described from Panesthia, a genusof subsocial wood cockroaches. Paradiplogynium panesthia Womersley, originally collected from Panesthia cribrata in NewSouth Wales, is redescribed. The new mite species are Paradiplogynium caitlinae sp. nov., Paradiplogynium damieni sp. nov.and Paradiplogynium elizabethae sp. nov. from Panesthia tyroni tryoni; Paradiplogynium isaaci sp. nov. from Panesthia cri-brata; Paradiplogynium kaii sp. nov. from Panesthia sloanei; and Lobogyniella harrynahmani sp. nov. from Panesthiaancaudellioides. Paradiplogynium and Lobogyniella are re-diagnosed and a key to Paradiplogynium is provided. EachPanesthia species has a large and a small species of diplogyniid mite associated with it. In two instances, geographically distanthost populations had different species of mite. Mites are restricted to a single host, except the widespread species Paradiplogy-nium nahmani, which is now known from Titanolabis colossea (Dermaptera), Pan. ancaudellioides, Pan. cribrata and Pan. sloanei.